Controlling crop pests and diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Controlling pests and diseases by Rosalyn Rappaport with cartoons by Robin Edmonds 1992 106pp ISBN 0 333 57216 5 Pbk The Macmillan Press Ltd 4 Little Essex Street London WC2R 3LD UK Also available from CTA